2017
DOI: 10.1038/s41598-017-05800-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Male-Male Mounting Behaviour in Desert Locusts during Infection with an Entomopathogenic Fungus

Abstract: Same-sex sexual behaviour occurs across diverse animal taxa, but adaptive explanations can be difficult to determine. Here we investigate male-male mounting (MMM) behaviour in female-deprived desert locust males infected with the entomopathogenic fungus Metarhizium acridum. Over a four-week period, infected locusts performed more MMM behaviours than healthy controls. Among infected locusts, the probability of MMM, and the duration of time spent MMM, significantly increased with the mounting locust’s proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…This male-male mounting behaviour is rather common in the absence of females, and our results indicate that the observed change in male behaviour was mediated by linseed oil. This result differs from that of Clancy et al [20], who observed an increase in the frequency of male-male mounting (MMM) behaviour in desert locust males suffering from Metarhizium acridum, a fungal infection. This reduction in MMM is similar to the effect caused by "phenylacetonitrile" (PAN, also known as benzyl cyanide), which is a mature male volatile that prevents males from being mounted (homosexuality) by other males [5,21].…”
Section: Discussioncontrasting
confidence: 99%
“…This male-male mounting behaviour is rather common in the absence of females, and our results indicate that the observed change in male behaviour was mediated by linseed oil. This result differs from that of Clancy et al [20], who observed an increase in the frequency of male-male mounting (MMM) behaviour in desert locust males suffering from Metarhizium acridum, a fungal infection. This reduction in MMM is similar to the effect caused by "phenylacetonitrile" (PAN, also known as benzyl cyanide), which is a mature male volatile that prevents males from being mounted (homosexuality) by other males [5,21].…”
Section: Discussioncontrasting
confidence: 99%
“…These proteins enhance the ability of M. acridum to adapt to different conditions (Moisan et al, 2019). Biocontrol workers have also tried to add incidental substances, such as neem seed oil, to fungal pesticides to develop new formulations with increased lethality to locusts (Clancy et al, 2017;Shi et al, 2019). After years of follow-up investigation, scientists have found that the natural prevalence rate of fungal diseases in locust swarms is very low, and the natural susceptibility rate in African grassland locust swarms is about 2-6%.…”
Section: Locust Biological Controlmentioning
confidence: 99%
“… 24 , 30 , 34 ). However, fungal infection affects traits related to reproduction in both male and female locusts 4 , 35 , 36 ; and fever temperatures themselves have been shown to affect male mating behaviours (but not survival or female fecundity) 37 , and to cause shifts towards the solitarious behavioural phase state in offspring 38 . Therefore, it is important that future studies focus on males, females, and offspring for a complete understanding of the costs and benefits that may drive the adaptive deployment of fever responses (see also 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our intention was to use male locusts only, to control for fungal inoculant dose in relation to body size/mass, as female locusts are larger than male locusts (c.f. 24 , 30 , 34 , 35 ). However, a small number of females were included in our first dose-response experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation